Assessment of curing temperatures to early predict the 28-day mechanical properties for recycle aggregate mixed concrete production. (10th February 2018) - Haque, M. Aminul; Bhowmik, Shuvo; Jahin, Mohsina Ferdous
Abstract: The recycle aggregate concrete construction is a promising way towards sustainable construction through recycling as an eco-friendly product. For this purposes, this paper presents the results of a study to investigate the effect of curing temperatures on the strength properties of concrete containing various percentage of recycle coarse aggregate as the substitution of natural aggregate. The representative concrete specimens were prepared on the basis of six mixes such as three specific design strength 21 MPa, 24 MPa, 28 MPa and three specific mix proportion 1:1:2, 1:1.5:3 and 1:2:4. The samples were cured in fully immersion condition with 100 °C, 50 °C and 26 °C temperatures. Results indicated that early strength development in the surrogate specimens cured by 100° C exhibited higher than that cured by 50° C and 26° C. Even, about 75–85% mechanical strength was obtained at 10.5 h in the specimens for 21 MPa, 24 MPa and mixture 1:2:4; and 78–90% was gained at 14hrs for 28 MPa, 1:1:2 and 1:1.5:3in relation to the 28 days strength cured by 100° C. This study also found the 30% recycle coarse aggregate substitution of the total volume of natural aggregate as optimum that satisfies the required strength performance of the six mixes. In addition, power equation model possessed strong potential for the early prediction of 28-day strength propertiesand justifies against the statistical point of view for interpreting the strength incremental factor variation profile with accelerated curing ages. Consequently, mechanical strength of target mixes can be early predicted using the proposed model equation using 100° C curing temperature in economical concreteconstruction and supports in reducing disposal concerns. Highlights: Demolish solid wastes were used as the partial replacement of natural aggregate. Six mixes were adopted to analyze the strength of the surrogate specimens. The effect of curing temperature on the strength of green concrete was observed. Boiling water curing method exhibited rapid gain of strength at early stage. Results revealed that 25% solid wastes could be substituted in all cases of mixes.